Complex life under the McMurdo Ice Shelf, and some speculations on food webs. Issue 2 (18th March 2019) - Kim, Stacy
Abstract: Habitats under ice shelves are minimally explored, primarily because of technological limitations. These areas are separated from photosynthetic primary productivity by thick ice and distance to open water. Nevertheless, a diverse macrofaunal benthic community was discovered at 188 m depth, 80 km back from the edge of the McMurdo Ice Shelf. The general habitat was fine sediment with occasional dropstones, and dominant taxa were polychaetes and brittle stars, with alcyonacean soft corals and anemones on hard substrates. Gelatinous animals were abundant near the seafloor, and possibly part of a food web that supports the benthic community.